Potency of Stirred Microfiltration Cell in Separation of Fermented Beans as Protein Isolate for Natural Source of Folic Acid - Aspiyanto Aspiyanto; Agustine Susilowati; Puspa Dewi Lotulung; Hakiki Melanie; Yati Maryati (Universitas Gadjah Mada, 2019)
Protein isolate from soy bean (Glycine soja L.) tempeh, mung bean (Phaseolus radiatus L.) tempeh and kidney bean (Phaseolus vulgaris L.) tempeh are natural source of folic acid with main role in brain smartness. 0.15 µm microfiltration (MF) membrane fitted in dead-end stirred microfiltration cell (SMFC) was able to separate protein isolate from three (3) kinds of tempeh at stirrer rotation speed 400 rpm, room temperature and pressure 40 psia for 30 minutes. The result of experimental work showed that SMFC had potential use in separation of protein isolate affected by kinds of bean and membrane performance on isolate composition in retentate and permeate. SMFC was able to retain better protein isolate in retentate than that passing across permeate. Retentate of protein isolate from soy bean tempeh, mung bean tempeh and kidney bean tempeh had subsequently compositions of folic acid 362.07, 254.07 and 506.07 µg/mL, total solids 5.56, 4.08 and 1.82 %, N-Amino 4.34, 3.36 and 0.56 mg/mL, and dissolved protein 0.79, 0.34 and 0.72 mg/mL. In this process condition, SMFC was able to increase folic acid in protein isolate retentate of soy tempeh of 0.59 times, mung bean tempeh of 1.1 times and kydney bean tempeh of 1.42 times before purification process in retentate. Based on both SMFC performance and efficiency, all the best purification optimization were obtained kidney beans tempeh. Identification of monomer of kidney bean tempeh protein isolate gave monomers of folic acid, glutamic acid and folic acid fractionation with molecular weight of 443.5797, 148.1643 and 221.2132 Da. and relative intensity of 1.28, 50.11 and 7.05 %, respectively.